Electrical Technology Curriculum: An Analysis of Educational Degrees and Vocational Instructor Roles for 21st Century Skills - Pullteap, Saroj (ARU Research Journal Humanities and Social Sciences, 2026)
In this academic study, the objective is to investigate the different strategies, developments, and regulations of electrical technology curricula within educational institutions in Thailand and internationally. Consequently, the study analyses 2 qualification degrees: the Bachelor of Technology degree (B.Tech.) and the Bachelor of Science in Technical Education degree (B.S.Tech.Ed.), evaluating their respective curricular frameworks’ strengths and weaknesses. Moreover, this investigation intends to reveal how curriculum structure affects the quality of vocational instructor preparation on a national scale, especially within the framework of 21st-century education that emphasizes the 21st century skills. Besides, the analysis examines the role of curricula in promoting economic and social progress, as well as enhancing national competitiveness amid Industry 4.0 and the transition to a digital economy. However, the analytical results indicated that electrical technology curricula are vital in providing vocational teachers with the key skills essential for teaching both the theoretical and practical components, thereby meeting the diverse requirements of educational institutions and ensuring alignment with current labor market expectations. In addition, the comparative examination between a couple of degrees showed that the Bachelor of Science in Technical Education (B.S.Tech.ED.) curricula effectively prepare graduates with pedagogical foundations, while the Bachelor of Technology (B.Tech.) curricula enhance practical competencies and workplace skills. The study further identifies that faculty development and instructor proficiency are essential factors influencing curriculum quality and educational results. Also, an integrated curriculum and continuous faculty development will cultivate vocational educators committed to lifelong learning, adaptability to technological advancements, and the delivery of innovative instruction aligned with real workplace needs. Accordingly, this article presents strategic recommendations and actionable guidelines for enhancing and refining electrical technology curricula to achieve superior quality, strengthen alignment with labor market requirements, and remain current with the evolving needs of educational institutions, employers, and national development objectives within Industry 4.0.